PENDEKATAN METODE DAKWAH OLEH PENYULUH AGAMA ISLAM NON PNS DI KECAMATAN SIMOKERTO TERHADAP RELIGIUSITAS PADA JAMAAH LANJUT USIA DI MAJELIS TAKLIM AL-HIDAYAH - Zarnuji, Aqib (RADIX: Jurnal Filsafat dan Agama, 2023)
The activities of the Al- Hidayah taklim assembly in Simokerto district are held every Thursday afternoon from 15.00 Wib to 16.00 Wib. Consisting of congregations, the majority of whom are elderly who are fostered by non PNS Islamic religios instuctors in simokerto district. The problem in this study is how are the characteristic of the elderly congregation and the model of the dakwah aproanch used by non PNS Islamic religious instrctors in conducting dakwah to elderly congregation. The method used in this study uses qualitative methods. Data collection techniques namely, observation, interview and documentation. Meanwhile in data processing the are several ways as follows: 1) data reduction, 2) selecting data, 3) data analysis, 4) data presentation and 5) drawing conclusions. The dakwah approach model used by non PNS Islamic religios instructors in Simokerto District for elderly congregation in the Al-Hidayah assembly is using a social approach model (bi al hal), an education approach model, a cultural education model, a personal approach model (fardiyah) and a personal approach model (fardiyah), group ja,’iyah